Analysis of Public Perception Regarding Public Service Information in Helvetia Village - Risda Mega Riana Br Sembiring; Miftha Rizkina; Ayu Kurnia Sari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze public perception regarding the effectiveness of public service information delivery in Helvetia Village through a hybrid information system (announcement boards and WhatsApp) based on the Good Governance framework (Transparency and Accountability). The method used is descriptive qualitative with triangulation data collection techniques including in-depth interviews, observation, and documentation. The results indicate that public perception of the information delivery system tends to be poor, triggering the